Mood in Parkinson's disease: From early‐ to late‐stage disease. (20th November 2020) - Santos‐García, Diego; De Deus, Fonticoba T.; Cores, Bartolome C.; Valdés, Aymerich L.; Suárez, Castro E.; Aneiros, Ángel; Jesús, Silvia; Aguilar, Miquel; Pastor, Pau; Planellas, Lluís; Cosgaya, Marina; García, Caldente J.; et al.
Abstract: Background: Although depression is known to be frequent in Parkinson's disease (PD), it is unclear how mood can change and/or impact on patient's quality of life (QoL) over time. Our aim was to analyze the frequency of depression, mood related factors and the contribution of mood to a patient's QoL perception in regard to disease duration. Methods: PD patients recruited from the COPPADIS cohort from January 2016 to November 2017 were included in this cross‐sectional study. Three groups were defined: <5 years (Group A); from 5 to <10 years (Group B); ≥10 years (Group C). Analysis with well‐planned linear regression models was conducted to determine how different factors contribute to mood (Beck Depression Inventory‐II [BDI‐II] as dependent variable), to health‐related QoL (39‐item Parkinson's Disease Questionnaire [PDQ‐39SI] as dependent variable) and to global QoL (European Health Interview Survey – Quality of Life Eight‐Item Index [EUROHIS‐QOL8] as dependent variable). Results: Six hundred and sixty‐three PD patients (62.6 ± 8.9 years old, 59.6% males) were included: Group A, 50.1% ( n = 332); Group B, 33.3% ( n = 221) and Group C, 16.6% ( n = 110). There were no differences between the three groups in terms of the frequency of depressive symptoms nor the frequency of depression type (major vs. minor vs. subthreshold) ( p = 0.729). However, the unique percent variance of PDQ‐39SI and EUROHIS‐QOL8 explained by BDI‐II total score was 2 (23.7%) and threefold (26.9%), respectively, in Group C compared to the other two groups. EUROHIS‐QOL8 total score provided the highest unique contribution to mood (16.8%). Conclusions: Although depression‐type frequency does not appear to change over time in PD; the contribution of mood on QoL perception is greater in patients with longer disease duration.